The Therapeutic Potential of Human Umbilical Mesenchymal Stem Cells From Wharton's Jelly in the Treatment of Rat Peritoneal Dialysis‐Induced Fibrosis. (30th December 2015) - Fan, Yu-Pei; Hsia, Ching-Chih; Tseng, Kuang-Wen; Liao, Chih-Kai; Fu, Tz-Win; Ko, Tsui-Ling; Chiu, Mei-Miao; Shih, Yang-Hsin; Huang, Pei-Yu; Chiang, Yi-Chia; Yang, Chih-Ching; Fu, Yu-Show
Abstract : Peritoneal fibrosis is a complication of continuous, ambulatory peritoneal dialysis in patients with end‐stage renal disease who are undergoing long‐term peritoneal dialysis. Intraperitoneal injection of human umbilical mesenchymal stem cells (HUMSCs) in rats ameliorated peritoneal dialysis/methylglyoxal‐induced abdominal cocoon formation, peritoneal fibrosis, inflammation, neoangiogenesis, and ultrafiltration failure. Abstract : A major complication in continuous, ambulatory peritoneal dialysis in patients with end‐stage renal disease who are undergoing long‐term peritoneal dialysis (PD) is peritoneal fibrosis, which can result in peritoneal structural changes and functional ultrafiltration failure. Human umbilical mesenchymal stem cells (HUMSCs) in Wharton's jelly possess stem cell properties and are easily obtained and processed. This study focuses on the effects of HUMSCs on peritoneal fibrosis in in vitro and in vivo experiments. After 24‐hour treatment with mixture of Dulbecco's modified Eagle's medium and PD solution at a 1:3 ratio, primary human peritoneal mesothelial cells became susceptible to PD‐induced cell death. Such cytotoxic effects were prevented by coculturing with primary HUMSCs. In a rat model, intraperitoneal injections of 20 mM methylglyoxal (MGO) in PD solution for 3 weeks (the PD/MGO 3W group) markedly induced abdominal cocoon formation, peritoneal thickening, and collagen accumulation. Immunohistochemical analyses indicated neoangiogenesis and significant increase in the numbers of ED‐1‐ and α‐smooth muscle actin (α‐SMA)‐positive cells in the thickened peritoneum in the PD/MGO 3W group, suggesting that PD/MGO induced an inflammatory response. Furthermore, PD/MGO treatment for 3 weeks caused functional impairments in the peritoneal membrane. However, in comparison with the PD/MGO group, intraperitoneal administration of HUMSCs into the rats significantly ameliorated the PD/MGO‐induced abdominal cocoon formation, peritoneal fibrosis, inflammation, neoangiogenesis, and ultrafiltration failure. After 3 weeks of transplantation, surviving HUMSCs were found in the peritoneum in the HUMSC‐grafted rats. Thus, xenografts of HUMSCs might provide a potential therapeutic strategy in the prevention of peritoneal fibrosis. Significance: This study demonstrated that direct intraperitoneal transplantation of human umbilical mesenchymal stem cells into the rat effectively prevented peritoneal dialysis/methylglyoxal‐induced abdominal cocoon formation, ultrafiltration failure, and peritoneal membrane alterations such as peritoneal thickening, fibrosis, and inflammation. These findings provide a basis for a novel approach for therapeutic benefits in the treatment of encapsulating peritoneal sclerosis.